Ծռազատկի մասին արձագանքները հայ եւ օտար սկզբնաղբիւրներում - Ղարիբեան, Կարօ սրկ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Ввиду различных календарных расчетов в течение одного 532-летия 4 раза случалось так, что день праздника Пасхи различных Церквей не совпадал. Так называемые «Кривые пасхи» («Цразатик») создавали большие проблемы, так как были связаны с днем празднования Святого Воскресения, занявшего центральное место в христианском календаре. День праздника Святого Воскресения является ориентиром для большей части передвижных праздников, следовательно, при несовпадении Пасхи отличались также дни других передвижных праздников. В данной статье впервые собраны и рассмотрены почти все библиографические свидетельства об исторических разногласиях, связанных с «Кривой пасхой», которые имеют важное значение в деле изучения и интерпретации взаимоотношений между Армянской и соседними Церквями.Due to various calendar calculations, in the same year of 532, the celebration day of the Easter did not coincide four times in various churches. Different dates of the Easter celebration caused great troubles, because they were connected to the Feast of Holy Resurrection, which occupies a central place in the Christian feastcalendar. The day of the Feast of Holy Resurrection is an indicator for most of the movable feasts; therefore if the Easter date did not coincide, the dates of other movable feasts did not coincide, either. This article for the first time brings together and examines almost all the literary evidences related to the historical events concerning different dates of the Easter celebration, which are important for the study and interpretation of the relations between the Armenian Church and neighboring churches.
Keywords: Armenian church; Liturgy and Ritual; Կրօնագիտութիւն